Defining the “Correlate(s) of Protection” to tick-borne encephalitis vaccination and infection – key points and outstanding questions - Ackermann-Gäumann, Rahel; Lang, Phung; Zens, Kyra D. (Frontiers in Immunology, 2024)
Tick-borne Encephalitis (TBE) is a severe disease of the Central Nervous System (CNS) caused by the tick-borne encephalitis virus (TBEV). The generation of protective immunity after TBEV infection or TBE vaccination relies on the integrated responses of many distinct cell types at distinct physical locations. While long-lasting memory immune responses, in particular, form the basis for the correlates of protection against many diseases, these correlates of protection have not yet been clearly defined for TBE. This review addresses the immune control of TBEV infection and responses to TBE vaccination. Potential correlates of protection and the durability of protection against disease are discussed, along with outstanding questions in the field and possible areas for future research.